Foreign body punctured the spleen: An incidental diagnosis - İnal-Aslan, Gizem; Ötgün, İbrahim; Güney, Lütfi Hakan; Hiçsönmez, Akgün (The Turkish Journal of Pediatrics, 2017)
A foreign body can enter the body via penetration through the skin. In the presented case, a broken syringe needle was found and removed from the splenic parenchyma. In order to prevent such iatrogenic injuries, which could have fatal consequences, the hospital staff must give particular care in the handling of sharp FBs.
Keywords: foreign body; infant; penetration; spleen